Prospek Masa Depan Bank Syariah di Indonesia Pasca Pemergeran Bank-Bank Syariah BUMN - Eka Kurniasari (Rechtenstudent, 2021)
The progress of Islamic banking is a parameter for the sustainability of the sharia economy, Sharia Bank has a very important function, namely as a collection and distribution of funds to the public based on Islamic religious law, the sharia banking division, namely BRI Syariah, Mandiri Syariah and BNI Syariah is expected to be able to boost the existence of Islamic banks whose existence is very far behind when compared to Conventional Banks. The purpose of this study is to analyze the development of Islamic banking in Indonesia after the three sharia bank margins. The method used in this study is   analysis. The role of the Sharia Bank has received full attention from the government and is expected to be able to strengthen the national economy and contribute as an international bank.